Stereoselective synthesis of beta-C-Allyl- and beta-C-propargyl-D-arabinofuranosides - Ramana, C. V.; Narute, Sachin B.; Gonnade, Rajesh G.; Patil, Rahul S. (Synthesis-Stuttgart, 2008)
The stereoselective synthesis of beta-configured C-allyl- and C-propargyl-D-arabinofuranosides (4,7-anhydro-1,2,3-deoxy-D-gluco-oct-1-enitols and -oct-1-ynitols) was addressed by employing allylation/propargylation of a dialdofuranose under aqueous Barbier reaction conditions and acid-catalyzed furan ring transposition of 5-O-mesyl-manno-oct-7-eno- or 5-O-mesyl-manno-oct-7-ynofuranoside derivatives.
Keywords: Allylation; Barbier reaction; C-glycoside; D-mannose; propargylation; Ring transposition

Synthesis of chenopanone - Deore, Prashant S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Starting from glyoxalic acid, a facile three step approach to chenopanone has been described utilizing the Barbier reaction as a key step.
Keywords: acid hydrolysis; Barbier reaction; chenopanone; condensation; Glyoxalic acid; isovaleraldehyde; synthesis